Analysis of Sapardi Djoko Damono’s Translation of the Poem ‘A Dream of Washed Hair’ by Rhyll McMaster - Eka Ugi Sutikno; Ghiast Nurdini Fauziah; Liyana Nur Aini; Rizqitasari Any Futhurisma; Wantiyah Nurkhanifah (English Education Department, 2022)
The poem is the aesthetic work that can translate by target language translation; however, there is an exception on Sapardi Djoko Damono’s translation of the poem ‘A Dream of Washed Hair’ by Rhyll McMaster because there is numerous semantic translation as the primary method. This article would like to analyze Sapardi Djoko Damono’s translation of the poem ‘A Dream of Washed Hair’ by Rhyll McMaster because the subjugated of this work by source orientation language translation, especially semantic translation. This study uses a qualitative descriptive type of research because it describes the data in writing and analysis of translation. The method in this qualitative research uses the method of content analysis. The analysis has resulted from the numerous methods employed to translate the text above, including two faithful translation methods, three free translation methods, six semantics translation methods, one word-for-word translation method, and two literal translation methods.